KESANTUNAN BERBAHASA ANTARA GURU DAN SISWA DALAM PROSES PEMBELAJARAN DI SMP NEGERI 1 KOTA TERNATE - Anwar Ismail; Suhardi Kasim (Universitas Khairun, 2022)
The purpose of this study was to identify the types of impolite utterances uttered by teachers and students in the learning process and to identify the types of politeness maxims that were violated by teachers and students in the learning process at SMP Negeri 1 Kota Ternate, and using politeness scale approach to determine the types of polite speech. The method used in this research is descriptive qualitative method. This study uses three data collection techniques, namely; 1) technique of observation (observation). 2) the technique of observing and taking notes. 3) technique of recording (record). The research results show that; six (6) politeness maxims conveyed by Leech, all maxims are violated by teachers and students in the learning process in class. The maxim that is often flouted is the maxim of modesty/simplicity and the least flouted is the maxim of conformity/agreement. Violations of politeness maxims are more frequently violated by teachers than by students. All violations of these maxims are carried out in the learning process in class. The politeness scale is a measure to determine the level of politeness in a speech. The politeness scale is used as a measure of politeness in a speech adapted to the context of the speech itself.